A comparison, using dsRNA analysis, between beet soil-borne virus and some other tubular viruses isolated from sugar beet - Hutchinson, P. J.; Henry, C. M.; Coutts, R. H. A. (Journal of General Virology, 1992)
Double-stranded RNA preparations from Chenopodium quinoa leaves inoculated with two English isolates of beet soil-borne virus (BSBV), BSBV-N and BSBV-452N, a French isolate of beet necrotic yellow vein virus (BNYVV), a Swedish isolate of a tubular beet virus (86–109) or a Belgian isolate of a similar virus (1530) were compared following separation on non-denaturing polyacrylamide gels. The dsRNAs of BNYVV differed in mobility from those isolated from tissue infected with the other four tubular beet viruses, which possessed three major dsRNA species. The degree of sequence identity between BNYVV, BSBV-N, 86–109 and 1530 was investigated by RNA-RNA blot hybridization using 32P-5′ end-labelled probes. Reciprocal hybridization experiments revealed similarity between the BSBV-N, 86–109 and 1530 isolates, but none between these isolates and BNYVV.